2017
DOI: 10.1177/0956797616687812
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Executive Function: A Two-Generation Cross-Cultural Comparison of Samples From Hong Kong and the United Kingdom

Abstract: Although Asian preschoolers acquire executive functions (EFs) earlier than their Western counterparts, little is known about whether this advantage persists into later childhood and adulthood. To address this gap, in the current study we gave four computerized EF tasks (providing measures of inhibition, working memory, cognitive flexibility, and planning) to a large sample ( n = 1,427) of 9- to 16-year-olds and their parents. All participants lived in either the United Kingdom or Hong Kong. Our findings highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 37 publications
5
60
1
Order By: Relevance
“…This effect was identified most consistently with regard to the EF facet of inhibition. All eight studies that reported cross‐national comparisons between East Asian and Euro‐American children for inhibition measures reported significant findings for at least one inhibition subtest (Ellefson et al, ; Grabell et al, ; Lan, Legare, Ponitz, Li, & Morrison, ; Oh & Lewis, ; Sabbagh et al, ; Schmitt et al, ; Tran et al, ; Wang et al, ). Out of these eight studies, seven reported effect sizes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This effect was identified most consistently with regard to the EF facet of inhibition. All eight studies that reported cross‐national comparisons between East Asian and Euro‐American children for inhibition measures reported significant findings for at least one inhibition subtest (Ellefson et al, ; Grabell et al, ; Lan, Legare, Ponitz, Li, & Morrison, ; Oh & Lewis, ; Sabbagh et al, ; Schmitt et al, ; Tran et al, ; Wang et al, ). Out of these eight studies, seven reported effect sizes.…”
Section: Resultsmentioning
confidence: 99%
“…Ten publications administered shifting tasks in East Asian and Western samples, the most common being the Dimension Change Card Sort (DCCS; Zelazo, ). One of these studies did not find any cross‐national differences in shifting (Tran et al, ), three found effects on only one out of two subtests (Moriguchi, Evans, Hiraki, Itakura, & Lee, ; Oh & Lewis, ; Yang et al, ), and the remaining six found solely significant effects ( Ellefson et al, ; Imada, Carlson, & Itakura, ; Sabbagh et al, ; Schmitt et al, ; Wang et al, ; Weixler, ). The effect sizes varied between small to medium (three studies) and medium to large (four studies).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these results, Ellefson et al (2017) examined whether this advantage persists beyond childhood. They asked middle school students from Hong Kong and the United Kingdom and their parents to complete four executive-functioning tasks assessing inhibition, shifting, planning, and working memory.…”
Section: Studies On Specific Aspects Of Self-regulation In Cultural Cmentioning
confidence: 99%